Pengaruh Dana Alokasi Umum, Dana Alokasi Khusus dan Pendapatan Asli Daerah Terhadap Kemandirian Keuangan di Provinsi Papua - Priskila Titaley; Richard Patty; Pisi Bethania Titalessy (Universitas Cenderawasih, 2026)
This study aims to analyze the influence of General Allocation Fund, Special Allocation Fund, and Local Own-Source Revenue on the financial independence of districts and cities in Papua Province for the period 2018-2025. The method used is quantitative with panel data regression, combining 8 years of time series data and cross-section data from 9 districts and cities, resulting in 72 observational units. Model selection through the Chow Test and Hausman Test yielded the Fixed Effect Model as the best model, with hypothesis testing using t-test, F-test, and coefficient of determination. The results show that the average financial independence is only 4.86 percent (very low category). Partially, the General Allocation Fund has a negative and significant effect (prob. 0.0003), consistent with the flypaper effect theory; the Special Allocation Fund has no significant effect (prob. 0.3569); and Local Own-Source Revenue has a positive and significant effect (prob. 0.0000). Simultaneously, all three variables have a significant effect with an R² value of 98.19 percent. Keywords: General Allocation Fund, Special Allocation Fund, Local Own-Source Revenue, Financial Independence